Release films for manufacturing electrolyte membranes or membrane electrode assemblies

By using a single layer film composed of at least 95% by weight of syngastic polystyrene (sPS) as the support film, the problems of uneven peeling, pollution and high cost of the support film in the prior art in fuel cell production are solved, and efficient and economical support film application is achieved.

CN114072938BActive Publication Date: 2025-03-04W L GORE & ASSOC GK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980098333.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-07-11
Publication Date
2025-03-04
Estimated Expiration
2039-07-11

AI Technical Summary

Technical Problem

In the prior art, the supporting membrane has problems such as uneven peeling, contamination of the electrolyte membrane, high cost and insufficient structural integrity when producing polymer electrolyte fuel cells.

Method used

A single layer film containing at least 95% by weight of syngastic polystyrene (sPS) was used as the release film, and a peelable support film was formed by laminating with the ion exchange film.

Benefits of technology

The low-cost production of the support film is achieved, with sufficient mechanical strength, chemical resistance and heat resistance, and good peeling and adhesive properties, avoiding the deterioration of the electrolyte film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114072938B_ABST
    Figure CN114072938B_ABST
Patent Text Reader

Abstract

The present invention relates to a laminate comprising: (i) an ion exchange membrane comprising an ion exchange polymer; and (ii) a monolayer release film removably attached to at least one side of the ion exchange membrane, wherein the monolayer release film comprises at least 95% by weight of syndiotactic polystyrene (sPS). The present invention also relates to a method for producing the laminate, the use of the monolayer release film in producing an electrolyte membrane or a membrane electrode assembly, and a method for producing an electrolyte membrane or a membrane electrode assembly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate comprising a single-layer release film removably attached to an electrolyte membrane, a method for producing the laminate, the use of the single-layer release film in the production of an electrolyte membrane or a membrane electrode assembly, and a method for producing an electrolyte membrane or a membrane electrode assembly, such as a membrane electrode assembly of a polymer electrolyte fuel cell. Background Art

[0002] Fuel cells convert the chemical energy of a fuel (eg, hydrogen or methanol) into electrical energy through an electrochemical reaction of the fuel with oxygen or another oxidant.

[0003] All fuel cells contain a so-called membrane electrode assembly (MEA), which includes an ion exchange membrane (IEM) sandwiched between an anode electrode and a cathode electrode. The IEM is used as a solid electrolyte membrane in fuel cells. Ion exchange membranes are also used for the electrolysis of sodium chloride solutions to form chlorine and sodium hydroxide. In addition, IEMs are useful in flow batteries and in the fields of diffusion dialysis, water electrolysis, electrodialysis, and for pervaporation and vapor permeation separations.

[0004] Fuel cells are mainly classified according to the type of electrolyte. Examples of fuel cells are proton exchange membrane fuel cells (PEMFC, also known as polymer electrolyte membrane fuel cells, PEFC), alkaline fuel cells (AFC), phosphoric acid fuel cells (PAFC), molten carbonate fuel cells (MCFC) and solid oxide fuel cells (SOFC).

[0005] Polymer electrolyte fuel cells are particularly advantageous because they operate at lower temperatures than other fuel cells. In addition, polymer electrolyte fuel cells do not contain any of the corrosive acids found in phosphoric acid fuel cells.

[0006] PEMFC is produced by laminating a plurality of single cells, wherein each cell comprises a membrane electrode assembly, which comprises a stack of a polymer electrolyte membrane (ion exchange membrane) and a gas diffusion electrode attached to each surface of the electrolyte membrane. Each gas diffusion electrode comprises a laminate of an electrode catalyst layer (usually a platinum catalyst) and a gas diffusion layer. The gas diffusion layer (GDL) enables hydrogen or oxygen to enter the corresponding catalyst layer and is usually made of hydrophobized porous carbon paper / cloth, but other materials have also been proposed.

[0007] The electrolyte membrane of the PEMFC conducts only protons and the electrons formed at the anode are transferred from the anode to the cathode through an external circuit, thereby generating electrical energy. The electrolyte membrane of the PEMFC may include, for example, a perfluorosulfonic acid (PFSA) polymer, such as a tetrafluoroethylene / fluorovinyl ether copolymer having a sulfonic acid group (e.g., provided by DuPont ).

[0008] In order to increase PEM conductance and total PEMFC power output, there is a drive to reduce the thickness of the PEM. PEMs are typically very thin, such as 10 μm and 200 μm. However, reducing the PEM thickness may result in reduced structural integrity and handling issues during the manufacturing process. Therefore, the PEM is typically reinforced by additional reinforcement materials, such as porous reinforcement materials (e.g., expanded polytetrafluoroethylene (ePTFE) membranes) impregnated with electrolyte materials (e.g., PFSA).

[0009] For example, US 2011 / 020730 relates to a biaxially oriented film suitable as a reinforcing member for an electrolyte membrane for a polymer electrolyte fuel cell. The reinforcing member is part of the final PEM. The biaxially oriented film comprises syndiotactic polystyrene (sPS) and has a Young's modulus in at least one of the machine direction and the transverse direction in the range of 4,500 MPa to 8,000 MPa.

[0010] In order to facilitate processing and prevent the thin polymer electrolyte membrane from being deformed and destroyed (e.g., wrinkled or broken) during its production, transfer, storage, and processing, the polymer electrolyte membrane is usually arranged on a support film (also referred to as a backing layer, a release film, or a backing). The support film is used as a supporting substrate for forming a polymer electrolyte membrane. Thereafter, before the polymer electrolyte membrane is laminated with the electrode when manufacturing a fuel cell, the support film is separated (peeled off) from the polymer electrolyte membrane. Therefore, the support film is usually not present in the final fuel cell.

[0011] The peelable support film needs to have sufficient mechanical strength to withstand continuous roll-to-roll processing and sufficient peeling properties (peelability) to allow the support film to be easily peeled off from the membrane. However, there must still be sufficient adhesion to resist accidental separation of the support film from the membrane. The support film should not contaminate the electrolyte membrane and should have heat resistance (e.g., at temperatures of 130°C to 190°C), chemical resistance (e.g., acid resistance), anti-fouling properties, and dimensional stability.

[0012] EP 2422975 discloses a laminate comprising a release film made of a cycloolefin copolymer (COC) and a layer containing an ion exchange resin laminated on the release film. The laminate further comprises a substrate film laminated on the side of the release film opposite to the layer containing the ion exchange resin, such as a film made of polyethylene terephthalate (PET), polyethylene naphthalate (PEN) or polypropylene (PP).

[0013] JP 2014175116 A relates to a support film including a base layer formed of a synthetic resin (eg, polyester) having an elastic modulus of 100 to 1000 MPa at 150° C. and a release layer of a syndiotactic polystyrene (sPS) resin coated on at least one side of the base layer.

[0014] JP 2016096108 A relates to an electrolyte membrane structure, including an electrolyte membrane disposed on a supporting substrate membrane of syndiotactic polystyrene (sPS), having "high adhesion" on the side facing the electrolyte membrane structure compared to the back side of the supporting membrane. It is disclosed that the increased adhesion properties of sPS sheets are provided by applying a fluororesin coating on sPS. JP 2016096108 A relates to resin-coated sPS as a cheaper alternative to polytetrafluoroethylene (PTFE) and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA). In addition, JP 2016096108 A discusses winding a laminate of an electrolyte membrane and a PTFE or PFA membrane on a roll, which may cause the electrolyte membrane to separate from the supporting membrane due to the adhesion between the back surface of the membrane and the electrolyte membrane.

[0015] JP 2017081011 A relates to a laminated film for manufacturing a membrane electrode assembly. The laminated film includes a substrate layer (e.g., polyester, PET, or syndiotactic polystyrene (sPS) resin), a first layer containing an adhesive component (e.g., a chlorine-containing resin) applied to at least one surface of the substrate layer, and a second layer containing a release component (e.g., a cyclic olefin resin) laminated on the first layer.

[0016] US 2017 / 077540 describes a support film provided by introducing fluorine atoms into at least one surface of a substrate film, the substrate film being formed by one or more types of polymers selected from the group consisting of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyphenylene sulfide, polysulfone, polyether ketone, polyether ether ketone, polyimide, polyetherimide, polyamide, polyamide-imide, polybenzimidazole, polycarbonate, polyarylate and polyvinyl chloride. For example, fluorine atoms can be introduced by contacting the substrate film with fluorine gas.

[0017] Modifying the surface of the support membrane using an adhesive resin or otherwise on the side of the support membrane facing the electrolyte membrane may contaminate the electrolyte membrane, resulting in, for example, degradation of its proton conductivity. In addition, the detachment characteristics of the membrane may change over time due to chemical migration from the support membrane to the electrolyte membrane. In addition, modifying the surface of the support membrane using an adhesive resin or otherwise results in additional costs when manufacturing the support membrane. In addition, the support membrane may encounter problems with uneven peel strength and / or uneven thickness.

[0018] The production cost of the laminated support film is high. In addition, due to the adhesion between the back side of the substrate layer (e.g., PET) and the polymer electrolyte membrane, there may be problems of delamination of the support membrane or the electrolyte membrane being inadvertently peeled off (delaminated) from the support membrane when unrolling the roll of the polymer electrolyte membrane to which the laminated support membrane is adhered. In addition, wrinkles and curling may form, resulting in different thermal properties of the layers of the support membrane. In addition, the thickness of the multilayer (e.g., double-layer) laminate is generally about 50 μm or more.

[0019] Therefore, there is a need for a low-cost support membrane that meets the above requirements, such as having sufficient release and adhesion properties while avoiding degradation of the electrolyte membrane when laminating the support membrane layer to the electrolyte membrane. Summary of the invention

[0020] It has been found that a monolayer film comprising at least 95 wt.% of syndiotactic polystyrene (sPS) has the desired mechanical strength, chemical resistance and thermal resistance, as well as suitable peeling and adhesion properties to be advantageously used as a peelable support film, hereinafter referred to as a release film, in the production of an electrolyte membrane or a membrane electrode assembly. The electrolyte membrane or membrane electrode assembly can be used to manufacture electrochemical devices such as polymer electrolyte fuel cells, flow batteries, and multilayer membranes for electrolysis.

[0021] Another advantage of a monolayer release film comprising at least 95% by weight of syndiotactic polystyrene (sPS) is that its thickness can be less than 50 μm, for example in the range of 25 μm to 40 μm, and still provide sufficient mechanical strength. This means that when the laminate of the polymer electrolyte membrane and the monolayer release film made of sPS is wound on a roll, the weight and diameter of the roll are smaller than the roll of the support membrane laminate comprising a thicker laminate, and therefore the former will be easier to handle during transfer, storage and use in the manufacture of the membrane electrode assembly of the polymer electrolyte fuel cell.

[0022] Furthermore, single-layer membranes of syndiotactic polystyrene are less complex and inexpensive to produce, thereby achieving reduced manufacturing costs for the membrane electrode assembly compared to using multiple layers of support membranes.

[0023] Thus, according to a first aspect of the present invention, there is provided a laminate comprising an ion exchange membrane and a monolayer release film removably attached to at least one side of the ion exchange membrane, wherein the monolayer release film comprises at least 95 wt % syndiotactic polystyrene (sPS). The ion exchange membrane comprises an ion exchange polymer, such as a fluoropolymer comprising sulfonic acid side groups.

[0024] In one embodiment of the laminate, the ion exchange membrane is an electrolyte membrane, in particular a polymer electrolyte membrane.

[0025] In another embodiment of the laminate, the ion exchange membrane is a reinforced electrolyte membrane, in particular a reinforced polymer electrolyte membrane.

[0026] "Syndiotactic polystyrene (sPS)" refers to an ordered polystyrene with phenyl groups located on alternating sides of the hydrocarbon backbone. Syndiotactic polystyrene may contain unsubstituted styrene units or ring-substituted styrene units. Syndiotactic polystyrene made from unsubstituted styrene units is produced by Idemitsu Corporation of Japan under the trade name XAREC.

[0027] The syndiotactic polystyrene of the single-layer release film of the laminate disclosed herein may be unsubstituted syndiotactic polystyrene or ring-substituted syndiotactic polystyrene.

[0028] Examples of ring-substituted syndiotactic polystyrenes are syndiotactic poly(alkylstyrenes), syndiotactic poly(halogenated styrenes), syndiotactic poly(alkoxystyrenes), syndiotactic poly(phenylstyrenes), syndiotactic poly(vinylstyrenes), and syndiotactic poly(vinylnaphthalene). Examples of poly(alkylstyrenes) include poly(methylstyrene), poly(ethylstyrene), poly(propylstyrene), and poly(butylstyrene), such as poly(p-methylstyrene), poly(m-methylstyrene), and poly(p-tert-butylstyrene). Examples of poly(halogenated styrenes) include poly(chlorostyrene), poly(bromostyrene), and poly(fluorostyrene). Examples of poly(alkoxystyrenes) include poly(methoxystyrene) and poly(ethoxystyrene).

[0029] The syndiotactic polystyrene of the monolayer release film of the laminate disclosed herein is preferably unsubstituted syndiotactic polystyrene.

[0030] In some embodiments, the monolayer release film comprises a biaxially oriented syndiotactic polystyrene film.

[0031] The monolayer release film containing at least 95 wt% biaxially oriented syndiotactic polystyrene (sPS) is transparent and colorless. This helps to control foreign particles and contaminants by camera inspection in the manufacture of membrane electrode assemblies. In addition, the biaxially oriented film containing at least 95 wt% syndiotactic polystyrene (sPS) allows the film to have high tensile strength.

[0032] The syndiotactic polystyrene may be expanded syndiotactic polystyrene, in particular a biaxially oriented expanded syndiotactic polystyrene film.

[0033] The weight average molecular weight of syndiotactic polystyrene can be at least 10000g / mol.Preferably, the weight average molecular weight of syndiotactic polystyrene is in the range of 50 000g / mol to 2 000 000g / mol, more preferably in the range of 100 000g / mol to 1 000000g / mol, and most preferably, the weight average molecular weight of syndiotactic polystyrene is 100 000g / mol to 300000g / mol.In one embodiment, the weight average molecular weight of syndiotactic polystyrene measured as described below is about 177000g / mol.

[0034] In a second aspect of the present invention, a laminate is provided, comprising: (i) an ion exchange membrane comprising an ion exchange polymer; and (ii) a monolayer release film removably attached to at least one side of the ion exchange membrane, wherein the peel force of the monolayer release film is equal to or less than 500 mN / cm using the method for measuring described herein, and the surface energy is within 23 mJ / m 2 Up to 50mJ / m 2 within the range.

[0035] Preferably, the peel force of the single-layer release film is equal to or less than 150 mN / cm using the method for measuring described herein, and the surface energy is equal to or less than 23 mJ / m using the method for measuring described herein. 2 Up to 45mJ / m 2 within the range.

[0036] In order to make the single-layer release film removably attached to at least one side of the ion exchange membrane without causing any damage or irreversible deformation to the ion exchange membrane or the release film when the release film is removed, the single-layer release film preferably has a tensile modulus (Young's modulus) in at least one of the machine direction and the transverse direction in the range of 2000 MPa to 5000 MPa, preferably 2500 MPa to 4000 MPa. More preferably, the tensile modulus of the single-layer release film in the machine direction is 2500 MPa to 4000 MPa, and the tensile modulus in the transverse direction is in the range of 2500 MPa to 4000 MPa.

[0037] In some embodiments, the tensile strength of the single-layer release film in at least one of the machine direction and the transverse direction may be at least 50 MPa, preferably at least 90 MPa. More preferably, the tensile strength of the single-layer release film in the machine direction is at least 100 MPa and the tensile strength in the transverse direction is at least 100 MPa.

[0038] The average thickness of the single-layer release film may be in the range of 10 μm to 100 μm, for example, 10 μm to 50 μm. Preferably, the average thickness of the single-layer release film is less than 50 μm, for example, in the range of 25 μm to 45 μm or 25 μm to 40 μm.

[0039] In a third aspect of the present invention, a method for producing a laminate as disclosed herein is provided. The method comprises applying (e.g., coating or laminating) an ion exchange membrane on a monolayer release film in one or more steps. The step of applying can be performed by roll-to-roll processing.

[0040] In one embodiment, the method comprises:

[0041] applying a solution of the ion exchange polymer in the solvent to the monolayer release film to provide a wet coating of the ion exchange polymer on the monolayer release film; and

[0042] The solvent is removed by drying to provide an ion exchange membrane on a single-layer release film.

[0043] In another embodiment, the method comprises:

[0044] applying a solution of the ion exchange polymer in the solvent to the monolayer release film to provide a wet coating of the ion exchange polymer on the monolayer release film; and

[0045] applying a porous reinforcing material (e.g., expanded polytetrafluoroethylene) to the wet coating of the ion exchange polymer;

[0046] drying to remove the solvent;

[0047] applying a solution of an additional ion exchange polymer in the solvent to the porous reinforcing material; and

[0048] The solvent is removed by drying to provide an ion exchange membrane on a single-layer release film.

[0049] In a fourth aspect of the present invention, there is provided use of a monolayer film comprising at least 95 wt % syndiotactic polystyrene (sPS) as a release film in the production of an electrolyte membrane or a membrane electrode assembly, such as a membrane electrode assembly of a polymer electrolyte fuel cell.

[0050] In a fifth aspect of the present invention, there is provided a method for producing an electrolyte membrane or a membrane electrode assembly for a polymer electrolyte fuel cell, the method comprising providing a laminate as disclosed herein and separating a single-layer release film from an ion exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 One embodiment of a laminate as disclosed herein is shown.

[0052] Figure 2 Shown are the peel strength (indicative of peel properties) and surface energy (indicative of adhesive properties) for various plastic films measured using the methods described herein.

[0053] Figure 3 The use of a single-layer release film in producing a reinforced electrolyte membrane is shown. DETAILED DESCRIPTION

[0054] In a laminate as disclosed herein, a single layer release film removably attached to at least one side of an ion exchange membrane comprises at least 95 wt % syndiotactic polystyrene (sPS).

[0055] “Removably attached” means that in a laminate comprising a single-layer release film attached to an ion exchange membrane, the single-layer release film can be removed from the ion exchange membrane without causing any damage or irreversible deformation to the ion exchange membrane or the release film.

[0056] Figure 1 One embodiment of a laminate 1 is shown, which includes an ion exchange membrane 2 and a single-layer release film 3 removably attached to one side of the ion exchange membrane 2. The ion exchange membrane includes an ion exchange polymer.

[0057] The monolayer release film of the laminate as disclosed herein comprises at least 95 wt% (based on the total weight of the film) of syndiotactic polystyrene (sPS) and additives ranging from 0 wt% to 5 wt%, such as antioxidants, antistatic agents, agents that enhance film operability, adhesion modifiers, agents that improve extrusion characteristics, and / or agents that improve conductivity.

[0058] The monolayer release film preferably consists of a chemically uniform (homogeneous) polymer composition, which means that the release film is uncoated and without any chemical surface modification.

[0059] The single-layer release film may have a density gradient and / or a crystallinity gradient along the thickness direction of the film. Such a gradient provides a varying density and / or crystallinity of the film.

[0060] In some embodiments, the average thickness of the single-layer release film may be in the range of 10 μm to 100 μm, such as 10 μm to 50 μm, such as 12 μm, 25 μm, 35 μm or 50 μm. Preferably, the average thickness of the single-layer release film may be less than 50 μm, such as in the range of 25 μm to 45 μm or 25 μm to 40 μm.

[0061] In some embodiments, the peel force of a monolayer release film of a laminate disclosed herein may be equal to or less than 150 mN / cm (using the method for measuring described herein).

[0062] In some embodiments, the surface energy of a single-layer release film of the laminate disclosed herein may be between 23 mJ / m 2 Up to 50mJ / m 2 in the range of (using the method for measurement described herein), preferably in the range of 25 mJ / m 2 Up to 45mJ / m 2 or 30mJ / m 2 Up to 40mJ / m 2 within the range of (using the method described herein for measuring).

[0063] In some embodiments, the monolayer release film of the laminate disclosed herein may have: a tensile modulus in at least one of the machine direction and the transverse direction may be in the range of 2000 MPa to 5000 MPa (preferably in the range of 2500 MPa to 4000 MPa), a tensile strength in at least one of the machine direction and the transverse direction of at least 50 MPa, a peel force equal to or less than 150 mN / cm (using the method for measuring described herein), and a surface energy of 23 mJ / m 2 Up to 50mJ / m 2 range (using the methods described herein for measuring).

[0064] In some embodiments, the single-layer release film of the laminate disclosed herein may have a tensile modulus in at least one of the machine direction and the transverse direction in the range of 2500 MPa to 4000 MPa, a tensile strength in at least one of the machine direction and the transverse direction of at least 100 MPa, a peel force equal to or less than 150 mN / cm (using the method for measuring described herein), and a surface energy of 25 mJ / m 2 Up to 45mJ / m 2 range (using the methods described herein for measuring).

[0065] In some embodiments, the laminate consists of an ion exchange membrane and a single-layer release film. Therefore, the laminate according to the present invention is preferably a two-layer laminate.

[0066] The single-layer release film has a front side (first flat film surface) and a back side (second flat film surface) opposite to the front side. In the laminate, the front side of the single-layer release film is removably attached to the ion exchange membrane, and the back side of the single-layer release film is preferably uncovered (i.e., unlaminated and uncoated).

[0067] The front side may have a first surface roughness and the back side may have a second surface roughness, wherein the first surface roughness and the second surface roughness are different. Preferably, the first surface roughness provides a smooth surface and the second surface roughness provides a rougher surface. The higher the surface roughness of the back side of the release film, the less adhesion it provides to the ion exchange membrane, and thus reduces the risk of the electrolyte membrane detaching from the support membrane due to the adhesion between the back side of the release film and the electrolyte membrane.

[0068] For example, the front side of the single-layer release film may have a first surface roughness (arithmetic mean roughness, Ra) less than 0.10 μm and the back side of the single-layer release film may have a second surface roughness (Ra) greater than 0.05 μm. In particular, the front side of the single-layer release film may have a first surface roughness (Ra) less than 0.10 μm, and the back side of the single-layer release film may have a second surface roughness (Ra) equal to or greater than 0.10 μm, and the arithmetic mean roughness (Ra) can be measured by standard method ISO4287:1997.

[0069] The monolayer release film may be formed, for example, by melt extrusion. Some release films according to the invention are commercially available, for example from the Japanese company Kurabo Industries Ltd under the trademark For example HNL and sPS membrane sold by HN.

[0070] The single-layer release membrane is preferably adjacent to (ie, in direct contact with) the ion exchange membrane.

[0071] The ion exchange membrane laminated on the release film may be an electrolyte membrane, an electrode membrane, or a membrane electrode assembly in which an electrode membrane is bonded to each side of the electrolyte membrane.

[0072] In a particular embodiment, the ion exchange membrane is an electrolyte membrane, such as a polymer electrolyte membrane.

[0073] The ion exchange membrane laminated on the release film may be a reinforced electrolyte membrane, for example a reinforced electrolyte membrane comprising a porous reinforced membrane impregnated with an electrolyte. Thus, in a particular embodiment, the ion exchange membrane is a reinforced polymer electrolyte membrane.

[0074] The laminate in the present disclosure can be obtained by coating a solution of an ion exchange polymer in a solvent on a single-layer release film, thereby providing a wet coating of the ion exchange polymer on the single-layer release film, and thereafter removing the solvent by drying.

[0075] Figure 3A method for manufacturing an enhanced polymer electrolyte membrane is shown. The method includes applying a solution of an ion exchange polymer in a solvent to a monolayer release film 4, thereby providing a wet coating 5 of the ion exchange polymer on the monolayer release film 4. A reinforcing material 6 (e.g., an ePTFE membrane) is then applied to the wet coating 5, and the solvent is subsequently removed by drying. In a second coating step, a solution of an additional ion exchange polymer in a solvent may be applied. The solvent is removed in a second drying step, thereby providing a laminate 7 of an enhanced polymer electrolyte membrane (enhanced ion exchange membrane) 8 and a monolayer release film 4. The monolayer release film 4 can then be removed and the enhanced polymer electrolyte membrane 8 can be used to produce a membrane electrode assembly.

[0076] The thickness of the ion exchange membrane comprising the ion exchange polymer can be adjusted to a desired thickness by adjusting the concentration of the ion exchange polymer solution, or repeating the steps of coating and drying the ion exchange polymer solution.

[0077] When the ion exchange membrane containing the ion exchange polymer is an electrolyte membrane for a polymer electrolyte fuel cell, a single-layer release film such as a commercially available Alternatively, a method of heat-pressing a separately prepared solid polymer electrolyte membrane into a release film may be used.

[0078] When the ion exchange membrane comprising an ion exchange polymer is an electrode membrane for a polymer electrolyte fuel cell, a solution or dispersion comprising an electrode membrane component (catalyst ink) may be coated on a release film and then dried.

[0079] When the ion exchange membrane containing the ion exchange polymer is a membrane electrode assembly for a polymer electrolyte fuel cell as described above, the anode electrode membrane or the cathode electrode membrane is formed on a release film, and then the polymer electrolyte membrane is bonded to the electrode membrane by heat pressing, and the cathode electrode membrane or the anode electrode membrane may also be combined with the polymer electrolyte membrane. In the case of combining the electrode membrane with the polymer electrolyte membrane, conventionally known methods such as screen printing, spraying, and decaling may be used.

[0080] The ion exchange membrane is preferably a polymer electrolyte membrane for a polymer electrolyte fuel cell. Such an electrolyte membrane is not particularly limited as long as it has a high proton (H + ) conductivity and electrical insulation properties and also have airtightness.

[0081] The thickness of the polymer electrolyte membrane may be in the range from 5 μm to 200 μm. However, since the thickness of the polymer electrolyte membrane exerts a large influence on resistance, the thickness of the polymer electrolyte membrane is generally set in the range of 5 μm to 50 μm, and preferably 10 μm to 30 μm.

[0082] The thickness of the laminate comprising an ion exchange membrane and a single-layer release film as disclosed herein can be in the range of 15 μm to 200 μm, preferably 15 μm to 100 μm (e.g., 17 μm), and more preferably from 20 μm to 50 μm (e.g., 22 μm), for example 30 μm to 50 μm or 35 μm to 50 μm (e.g., 45 μm).

[0083] Suitable ion exchange polymers of the ion exchange membrane include, but are not limited to, fluorinated polymers further comprising sulfonic acid groups, carboxyl groups, phosphoric acid groups or phosphine groups. Typical examples of ion exchange polymers are perfluorinated sulfonic acid resins and perfluorinated carboxylic acid resins.

[0084] The ion exchange polymer of the polymer electrolyte membrane in the present invention is not limited to a completely fluorine-based polymer compound. It can also be a mixture of a hydrocarbon-based polymer compound and an inorganic polymer compound, or a partially fluorine-based polymer compound containing both CH bonds and CF bonds in the polymer chain.

[0085] Specific examples of hydrocarbon-based polyelectrolytes include polyamide, polyacetal, polyethylene, polypropylene, acrylic resin, polyester, polysulfone or polyether, each having an electrolyte group such as a sulfonic acid group introduced therein, and derivatives thereof; polystyrene having an electrolyte group such as a sulfonic acid group introduced therein; polyamide, polyamideimide, polyimide, polyester, polysulfone, polyetherimide, polyethersulfone or polycarbonate, each having an aromatic ring, and derivatives thereof; polyetheretherketone having an electrolyte group such as a sulfonic acid group introduced therein; and polyetherketone, polyethersulfone, polycarbonate, polyamide, polyamideimide, polyester or polyphenylene sulfide, and derivatives thereof.

[0086] Specific examples of the partially fluorine-based polyelectrolyte include polystyrene-graft-ethylenetetrafluoroethylene copolymer or polystyrene-graft-polytetrafluoroethylene, each having an electrolyte group such as a sulfonic acid group introduced therein, and derivatives thereof.

[0087] Specific examples of the all-fluorine-based polymer electrolyte membrane include Membrane (manufactured by DuPont), membrane (manufactured by Asahi Kasei Corporation) and Film (manufactured by Asahi Glass Co., Ltd.).

[0088] The inorganic polymer compound may be a siloxane-based or silane-based organosilicon polymer compound, and particularly an alkylsiloxane-based organosilicon polymer compound, and specific examples thereof include polydimethylsiloxane and y-glycidyl propyltrimethoxysilane.

[0089] The ion exchange membrane may comprise one type of ion exchange polymer or two or more ion exchange polymers. In embodiments of two or more ion exchange polymers, the polymers may be a mixture or as separate layers.

[0090] Suitable solvents for use with ion exchange polymers include, for example, alcohols, carbonates, THF (tetrahydrofuran), water, and combinations thereof.

[0091] The laminate of the present disclosure can be obtained by:

[0092] a) applying a solution of an ion exchange polymer in a solvent to the monolayer release film, thereby providing a wet coating of the ion exchange polymer on the monolayer release film;

[0093] b) removing the solvent by drying to provide an ion exchange membrane on a single-layer release film.

[0094] The ion exchange membrane can also include reinforcing materials, such as porous materials (ePTFE membranes), fiber materials or reinforcing particles. In one embodiment, the reinforcing material can be a porous membrane. In another embodiment, the reinforcing material can include fibers or particles.

[0095] The porous membrane may be defined by a morphological organization comprising a microstructure of elongated nodes interconnected by fibrils, the microstructure forming a structural network of voids or pores. A porous membrane such as expanded polytetrafluoroethylene (ePTFE) may be substantially impregnated with the ion exchange polymer such that the interior volume of the porous membrane becomes substantially closed, thereby rendering the membrane substantially air impermeable. The ion exchange polymer may also be present on one or both surfaces of the porous membrane.

[0096] The porous membrane may be expanded polytetrafluoroethylene having a porous microstructure, such as pores with an average size of about 0.05 to about 0.4 μm. The expanded polytetrafluoroethylene may have a porosity (void fraction) greater than 35%, such as in the range of 70% to 95%.

[0097] The solution containing the ion exchange polymer in the solvent can be applied to the reinforcing material by conventional coating techniques, including forward roller coating, reverse roller coating, gravure coating or doctor blade roller coating, as well as dipping, brushing, smearing and spraying, as long as the liquid solution can penetrate the voids and internal volume of the reinforcing material. Excess solution can be removed from the surface of the reinforcing material. The treated reinforcing material is then dried in an oven. The oven temperature can range from 60°C to 200°C, but preferably from 160°C to 180°C. Additional application steps and subsequent drying can be repeated until the reinforcing material becomes completely transparent, which corresponds to an ion exchange membrane with a Gurley number greater than 10,000 seconds. It is usually necessary to process 2 to 60 times, but the actual number of treatments depends on the concentration and thickness of the reinforcing material.

[0098] In some embodiments, the ion exchange membrane comprises expanded polytetrafluoroethylene impregnated with an ion exchange polymer such as perfluorosulfonic acid resin.

[0099] Alternatively, the laminated materials of the present disclosure may be prepared by Figure 3 The method shown comprises the following steps:

[0100] a) applying a solution of an ion exchange polymer in a solvent to a release film, thereby providing a wet coating of the ion exchange polymer on the release film;

[0101] b) applying a porous reinforcing material (e.g. expanded polytetrafluoroethylene) to the wet coating of the ion exchange polymer;

[0102] c) drying to remove the solvent;

[0103] d) applying a solution of a further ion exchange polymer in said solvent to the porous reinforcing material; and

[0104] e) The solvent is then removed by drying to provide an ion exchange membrane on a single-layer release film.

[0105] The electrode membrane for polymer electrolyte fuel cell is not particularly limited as long as it contains catalyst particles and ion exchange polymer. As ion exchange polymer, the polymer described for the above electrolyte membrane can be used. The catalyst is usually made of a conductive material, and the conductive material contains catalyst particles loaded thereon. The catalyst particles can have a catalytic effect on the oxidation reaction of hydrogen or the reduction reaction of oxygen. In addition to precious metals such as platinum (Pt), cobalt, iron, chromium, nickel or their alloys can also be used. The conductive material is suitably carbon-based particles, such as carbon black, activated carbon and graphite, and fine powder particles are particularly suitable. Its typical example includes by being formed on a surface area of ​​20m 2 / g or more of carbon black particles loaded with precious metal particles (such as Pt particles and alloy particles made of Pt and other metals) obtained. Regarding the catalyst used for the anode, since Pt has poor tolerance to poisoning by carbon monoxide (CO), when using a fuel containing CO such as methanol, it is preferred to use alloy particles made of Pt and ruthenium (Ru). The ion exchange polymer in the electrode membrane is a material that acts as a binder, which loads the catalyst to form the electrode membrane and forms a channel through which the ions generated by the catalyst migrate. As the ion exchange polymer, the material described above for the solid polymer electrolyte membrane can be used. The electrode membrane is preferably porous so that the fuel (such as hydrogen or methanol) can contact the catalyst as much as possible at the anode, and the oxidant gas (such as oxygen or air) can contact the catalyst as much as possible at the cathode. The amount of the catalyst contained in the electrode membrane is between 0.01 and 4 mg / cm 2 The range of is suitable, and preferably 0.1 to 0.6 mg / cm 2 within the range.

[0106] Example 1

[0107] Production of laminates made of ion exchange membranes on a single release layer

[0108] The ion exchange membrane was manufactured by a double coating process using a rod coater (K202 control coater, RK Print Coat Instrument Ltd.) and an annealing process in an oven.

[0109] The area density is about 3-6 g / m 2 The biaxially oriented expanded PTFE membrane (ePTFE) is first impregnated with an ionomer solution, such as Ionomer solutions (commercially available from DuPont, USA) were provided on peelable support films of various single-layer polymer films using a Mayer bar #5 (see Table 1). The wet ePTFE and polymer films were immediately dried in an oven at 160°C for 3 minutes (first pass) to remove the solvents (ethanol and water).

[0110] The membrane was then impregnated again with the ionomer solution using a Meyer rod #4 at room temperature and dried in an oven at the same temperature for 3 minutes (second pass).

[0111] The membrane was finally annealed in an oven at the same temperature for 3 minutes (third pass) without further coating. The thickness of the ion exchange membrane was about 10 μm.

[0112] Measurement of peel strength

[0113] The peel strength was measured by a 90 degree peel test (ASTM D6862, with the difference that the sample size and peeling speed were changed) using a tensile tester (AG-I, Shimadzu Corp.). First, the ion exchange membrane on the single-layer release film of various polymer films (see Table 1) was cut into 20 mm wide × 150 mm long by a cutting die. The release film side was glued to a Bakelite board with double-sided tape. The board was set on a tensile test fixture with a roller, which automatically slides the board during the peeling process. The fixture is mounted on the base of the tensile tester. One side of the membrane is clamped by the chuck of the tensile tester. The membrane is peeled off from the release film by pulling up the chuck at a speed of 15 mm / minute, and the peeling force is recorded. The peel strength is calculated as the average of three measurement points at a distance from 10 mm to 50 mm.

[0114] Measurement of surface energy

[0115] The surface energies of various polymer films used as release films were determined by a two-component model, including the measurement of contact angles with water and diiodomethane, respectively.

[0116] Each polymer film was placed on a glass plate and placed in a contact angle measuring device (DM-501, Kyowa Interface Science Co. Ltd.). 2.0 μL of solvent (water or diiodomethane) was dripped from the needle of the device (tefloncoat 22G). The contact angle was measured 1500 ms after self-dropping using the θ / 2 method (see Yang et al., "A method for correcting the contact angle from the θ / 2 method", Colloids and Surfaces A: Physical Chemistry and Engineering, Vol. 220, No. 1-3, June 20, 2003, pp. 199-210, DOI: 10.1016 / S0927-7757(03)00064-5). The surface energy of the plastic film is determined by using the Kaelble-Uy theory (DH Kaelble (1970) Dispersion-Polar Surface Tension Properties of Organic Solids, The Journal of Adhesion, 2:2, 66-81, DOI: 10.1080 / 0021846708544582).

[0117] result

[0118] The peel strength and surface energy of various polymer films, as measured using the methods described herein, are shown in Table 1. The relationship between peel strength and surface energy is also shown in Figure 2 (Except PBT and PP). The film thickness values ​​in Table 1 are either measured by a thickness gauge or the thickness provided by the supplier in the product data sheet.

[0119] Table 1

[0120]

[0121]

[0122] It was found that the two sPS membranes tested (supplied by Kurabo) HNL and HN) has the desired peeling and adhesion properties and is advantageously used as a single-layer peelable support film (single-layer release film).

[0123] Furthermore, the sPS film exhibits desirable chemical and heat resistance.

[0124] In addition, the sPS film has the required mechanical strength, which is advantageous for use as a peelable support film. Table 2 includes data provided by the supplier (measured using the JIS K7127 method).

[0125] Table 2

[0126]

[0127] According to the high temperature GPC (gel permeation chromatography) method, the measurement was performed using a measuring device HLC-8321GPC / HT (Tocoh Corporation). The weight average molecular weight of syndiotactic polystyrene of HNL. 20 ml of o-dichlorobenzene (including 0.025% BHT) was added to 20 mg of sample (sPS membrane). The sample was oscillated and dissolved at 145°C. The dissolved substance was then hot filtered using a sintered filter (1.0 μm pore size), and the filtrate was analyzed. The syndiotactic polystyrene of HNL has a weight average molecular weight of about 177 000 g / mol.

Claims

1. A laminate comprising: an ion exchange membrane comprising an ion exchange polymer; and A monolayer release film removably attached to at least one side of an ion exchange membrane, wherein the monolayer release film comprises at least 95% by weight of syndiotactic polystyrene (sPS), The single-layer release film has a front side and a back side opposite to the front side, the front side of the single-layer release film is removably attached to the ion exchange membrane, and the back side of the single-layer release film is unlaminated and uncoated. 2 . The laminate according to claim 1 , wherein the single-layer release film comprises a biaxially oriented syndiotactic polystyrene film. 3 . The laminate according to claim 1 , wherein the single-layer release film comprises expanded syndiotactic polystyrene. 4 . The laminate according to claim 1 , wherein the single-layer release film comprises syndiotactic polystyrene having a weight average molecular weight in the range of 100,000 g / mol to 300,000 g / mol. 5 . The laminate according to claim 1 , wherein the single-layer release film comprises unsubstituted syndiotactic polystyrene. 6 . The laminate according to claim 1 , wherein the tensile modulus of the single-layer release film in at least one of a machine direction and a transverse direction is in the range of 2000 MPa to 5000 MPa. 7 . The laminate according to claim 1 , wherein the single-layer release film has a tensile modulus of 2500 to 4000 MPa in a machine direction, and a tensile modulus in a transverse direction in a range of 2500 to 4000 MPa.

8. The laminate according to claim 1 or 2, wherein the single layer release film has a tensile strength of at least 50 MPa in at least one of the machine direction and the transverse direction.

9. The laminate according to any one of claims 1 or 2, wherein the single-layer release film has a tensile strength of at least 100 MPa in the machine direction and a tensile strength of at least 100 MPa in the transverse direction. 10 . The laminate according to claim 1 , wherein the laminate consists of an ion exchange membrane and a single-layer release film. 11 . The laminate according to claim 1 or 2 , wherein the ion exchange polymer is a fluorine-containing polymer having a side chain having a sulfonic acid group. 12 . The laminate according to claim 1 , wherein the average thickness of the single-layer release film is less than 50 μm.

13. The laminate according to claim 1 or 2, wherein the ion exchange membrane is an electrode membrane.

14. The laminate according to claim 1 or 2, the ion exchange membrane is an electrode assembly in which the electrode membrane is connected to each side of the electrolyte membrane.

15. The laminate according to claim 1 or 2, wherein the ion exchange membrane is an electrolyte membrane.

16. The laminate according to claim 15, wherein the ion exchange membrane is a reinforced electrolyte membrane.

17. A method for producing a laminate according to any one of claims 1 to 16, comprising the step of applying the ion exchange membrane on the single-layer release film.

18. The method of claim 17, wherein the step of applying the ion exchange membrane is performed by roll-to-roll processing.

19. The method of claim 17, wherein the step of applying the ion exchange membrane comprises: applying a solution of the ion exchange polymer in a solvent to the single-layer release film, thereby providing a wet coating of the ion exchange polymer on the single-layer release film; and The solvent is removed by drying to provide an ion exchange membrane.

20. The method according to claim 17, comprising applying a solution of the ion exchange polymer in a solvent to the single layer release film, thereby providing a wet coating of the ion exchange polymer on the single layer release film; and applying a porous reinforcing material to the wet coating of the ion exchange polymer; drying to remove the solvent; applying a solution of an additional ion exchange polymer in the solvent to the porous reinforcement material; and The solvent is removed by drying to provide the ion exchange membrane.

21. A method for producing a membrane electrode assembly for a polymer electrolyte fuel cell, comprising: Providing a laminate according to claim 14; and The single-layer release film is separated from the ion exchange membrane.

22. A method for producing an electrolyte membrane, comprising: Providing a laminate according to claim 15; and The single-layer release film is separated from the ion exchange membrane.

Citation Information

Patent Citations

  • Laminate and method for producing same

    EP2422975A1

  • Laminated film, method for producing the same, laminated body, and method for producing catalyst layer-electrolyte membrane composite

    JP2017081011A

  • Film for reinforcing electrolyte membrane of polymer electrolyte fuel cell

    US20110020730A1

  • Support film for solution film forming, and method for producing electrolyte membrane using same

    US20170077540A1

  • Laminate for fuel battery fabrication, manufacturing method thereof, and manufacturing method of fuel battery

    JP2014175116A